Europe's parking u-turn: from accommodation to regulation. - Kodransky, Michael; Hermann, Gabrielle (My University, 2011)
This paper is the second in a series of policy papers from ITDP on parking. The first paper, released in Spring 2010, focused on successful parking practices in U.S. cities. This paper reviews successful parking practices in European cities. Parking management is a critical and often overlooked tool for achieving a variety of social goals. For much of the 20th Century, cities in Europe, like cities in the rest of the world, used parking policy mainly to encourage the construction of additional off-street parking, hoping to ease a perceived shortage of parking.
Keywords: Individualverkehr; Parken; Verkehrsplanung; Verkehrsinfrastruktur; Straßenraum; Fahrradparken; Mobilitätsmanagement; Verkehrssteuerung